Solutions to improve the International payment by documentary credit at Sai Gon Thuong Tin Comercial Joint Stock Bank- Thang Long Branch,Graduation Thesis - Giang Thị Nga,Nguyễn Hồng Ngọc,Nguyễn Tùng Anh
Solutions to improve the International payment by documentary credit at Sai Gon Thuong Tin Comercial Joint Stock Bank- Thang Long Branch : Graduation Thesis / Giang Thị Nga; Nguyễn Hồng Ngọc, Nguyễn Tùng Anh co-supervisor .- H. : Banking Academy , 2012 .- 32 p. ; 28 cm